HUBUNGAN BERDIRI LAMA DENGAN KELUHAN NYERI PUNGGUNG BAWAH MIOGENIK PADA PEKERJA KASIR DI SURAKARTA - Nur Susanti; Hartiyah .; Daniek Kuntowato (Universitas Pekalongan, 2015)
Background: Stand up is both phisically and mentally. So the activities of the work done faster, stonger, and thoroughly. Stand for a long time is the most common from discomfort and fatigue low back pain myogenic in touch stress/back strain muscle, tendon, ligament, that usual do daily activities more like stand for a long time. Pain is blunt, the intensity is varies, often become chronic, it is localized or spread, around glutea. This pain is not accompanied by parestesi, the deficit, neurology. If you cough or sneeze, pain did’n spread to the limbs, back pain problems that aries due to stand for a long time to be a phenomenon often happens to workers, especially over the chasier right now. When standing are likely to be static in one the same position more than 20 minutes therefore use a little work while standing in a long timecaused the decline in efficiency, reduced work, and the fatigue. The purpose of this research is to find out if there is to do stand for a long timewith complaints of low back pain myogenic on the chasier at a shopping mall of goro assalam surakarta.Method : research design which use correlasi design with 30 people sample. The result of statistic parametric data analysis. By correlasi product moment method with computer program SSPS support.Resulth : the result is indicating that the relation standing by long time with low back pain myogenic complaints the chasier. By value P count < P value (0,013 < 0,05). It is suggested for workers to use a rest a possible. For example, relaxing or stretcing for a moment and doing sport when holiday. For a company, more attantion with the healthy of workers, especially about detection early complaint.Conclusions: there is a relation among standing long time and low back pain myogenic complaints the chasier in surakarta.Key word : standing long time, low back pain myogenic, chasier.